World Wide Video Festival 1985. - Kijkhuis, Den Haag; World Wide Video Festival, Den Haag (Den Haag : Kijkhuis, 1985)
Duguet, Anne Marie ; Stewart, David ; Duchaine, Andree ; Andre, Marie ; Body, Gabor ; Brasch, Thomas ; Decostere, Stefaan ; Dreher, Christoph ; Fagin, Steve ; Forch, Juan E. ; Gohard, Gislaine ; etc.
World Wide Video Festival 1985, Kijkhuis, Den Haag, 1985
Nederlands & Engels
boek